Pengaruh Terapi Hortikultura terhadap Tingkat Stres Lanjut Usia - Pratama, Afizal Yusa; Nurhidayah, Ninik (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Elderly is someone who enters the age of 60 years and over and experiences the aging process which results in physical, cognitive, emotional, social, and sexual changes that trigger stress in the elderly. Horticultural therapy is one of the effective nonpharmacological interventions to overcome stress problems. Objectives: The purpose of this study was to determine the effect of horticultural therapy on elderly stress levels. This type of research is quantitative research using a pre-experimental design with one group pretest-posttest. This research was conducted in RW 08 Sumber Village, Trucuk District, Klaten Regency. Methods: Data collection methods were interviews, questionnaires, observation, and documentation. The sampling technique used was purposive sampling with asample size of 30 respondents. The instrument used to measure stress levels was the Perceived Stress Scale (PSS). The majority of the research sample was in the elderly category with an age range of 60-74 years (96.7%), female (56.7%), married (76.7%), and had an elementary education level (53.3%). %). Results: The results of data analysis obtained t=7.763, p=0.000. There is an effect of giving horticultural therapy on the stress level of the elderly. Conclusion: Based on the results of this study, horticultural therapy is an effective way to overcome stress problems in the elderly. Keywords: Horticultural Therapy, Stress level, Elderly.